Advanced practice nurses' experiences and well‐being: Baseline demographics from a cohort study. (5th June 2020) - Wood, Emily; King, Rachel; Robertson, Steve; Allmark, Peter; Senek, Michaela; Tod, Angela; Ryan, Tony
Abstract: Aims: To create a cohort of advanced practice nurses from across the UK and to report the initial questionnaire including demographics, work experiences and well‐being. Background: In the UK, advanced nursing practice is not regulated. This has led to the concern that advanced nurses are working in very different ways with different levels of autonomy and support. Methods: Participants were recruited via university and Royal College of Nursing mailing lists, and social media adverts. They completed the initial questionnaire about their background and workplace, work experiences, credentialing and well‐being. Results: A total of 143 nurses were recruited to the cohort and 86 completed the survey. Over 40 job titles were reported, across five pay bands. Job title was not correlated with pay band ( p  = .988). Participant well‐being was not significantly different from the UK general population, but they reported high rates of work‐related stress (44.2%) compared with the National Health Service national average (37.9%). Conclusion: There is a wide disparity in pay, which is not reflected in title or setting. The high levels of work‐related stress require further exploration. Implications for nursing management: The range of experiences reported here should encourage managers to evaluate whether title, pay and support mechanisms for Advanced Practice Nurses in their organisations align with suggested national standards set by Royal Colleges and government departments.